The Islamic Response to Modernity and Ecological Crisis - Hidayati, Tri; Kurniawan, Wiwit (International Journal of Educational Research & Social Sciences, 2022)
The problem of the ecological crisis and various environmental issues that arise today cannot be separated from the role of religion and religious communities as entities that are in contact with the environment. Muslims as the largest number of people in Indonesia have an influenced by their lifestyle in the environment. Therefore, awareness of environmental preservation is an important thing to consider in the actions and behavior of Muslims. This study aims to reveal how Islam responds to environmental issues. This research is a literature study using discourse analysis. The results of the study show that Islamic thought provides a critique of modernity that is misguided, and it causes human domination over nature. In addition, there is an Islamic understanding of new interpretations of the doctrine that can build relationships between humans and others. Also, there are daily practices of Muslims that show respect for nature.